Women’s Access to Land in Mauritania : A Case Study in Preparation for the COP - Bal, Salamata; Baro, Mamadou; O'Sullivan, Niamh (World Bank, Washington, DC, 2015)
Mauritania is a vast country covering over a million square kilometers, where a relatively small population of 3.5 million people lives on just one-fifth of the country’s total area. With extremely advanced desertification, the country is particularly vulnerable to the impact of climate change and other external shocks. The main sources of income in Mauritania are agriculture, which is either irrigated or rain-fed, and livestock. This is especially the case in the Senegal River Valley, where people make their living farming, raising livestock, and fishing, while mining is prevalent in the north. Arable land is therefore one of the country’s main resources, but it is also a major source of contention due to increasing urbanization and the limited availability of arable land. This presentation relies on the key recommendations emphasized in the Land Governance Framework Report (LGAF), published by the World Bank in 2014. This report established a far-reaching and more inclusive national land policy that strengthens the security of land tenure for vulnerable groups, including women. This framework was the first to propose a national platform for all stakeholders, including women, to openly discuss and reach consensus around land issues. The inclusive workshops that were held by LGAF helped stimulate discussion at all levels, from civil society, both men and women, to senior officials, promoting a national debate on land issues with a strong gender perspective. The workshops were particularly beneficial for many female participants, as these women now have increased access to information about land issues in their own communities.